Understanding Process Equipment for Operators and Engineers - Lieberman, Norman P. (Elsevier, 2019)
Understanding Process Equipment for Operators and Engineers explains how process equipment functions. As problems often arise in plants that must be solved by unit engineers, this book offers successful solutions and methods for their implementation. The concepts explained are based on Norm Lieberman's personal, hands-on experience. Like you, Norm attended a university and was exposed to technical seminars which did not always provide the needed solutions. In this text, you will learn the functioning of a variety of equipment types, including Fired Heater Draft, Centrifugal Pump Head, Distillation Tray Efficiency, Vacuum Jets, Recip Compressors, Steam Turbines, Thermosyphon Circulation Reboilers and Air Cooler.
Keywords: Chemical plants -- Equipment and supplies.; Reliability (Engineering); Industrial equipment.; Maintainability (Engineering); elektronické knihy; electronic books